0583 Obesity-Associated Sleep Hypoventilation Syndrome and Adverse Post-Operative Bariatric Surgery Outcomes. (27th May 2020) - Chindamporn, P; Bena, J; Wang, L; Zajichek, A; Milinovich, A; Kaw, R; Kashyap, S; Cetin, D; Aminian, A; Kempke, N; Foldvary-Schaefer, N; Aboussouan, L S; et al.
Abstract: Introduction: Although obesity hypoventilation syndrome (OHS) is associated with right ventricular dysfunction and increased mortality, its contribution to post-bariatric surgery risk remains unclear due to non-systematic OHS assessments. We hypothesize that patients with obesity-associated sleep hypoventilation (OASH) have increased adverse post-bariatric surgery outcomes than those without. Methods: Patients undergoing polysomnography (PSG) prior to bariatric surgery at the Cleveland Clinic from 2011-2018 were retrospectively examined. OASH was defined by body mass index (BMI) ≥30kg/m 2 and either PSG-based end-tidal CO2 ≥45mmHg or serum bicarbonate ≥27mEq/L. The following were considered individually and as a composite outcome: ICU stay, re-intubation, tracheostomy, discharge disposition or 30-day readmission. All-cause mortality was also examined. Outcomes were compared using two-sample t-test or Wilcoxon rank sum test and Chi-square or Fisher exact test. A multivariable logistic regression model included age, sex, BMI, apnea hypopnea index(AHI) and diabetes to examine OAHS and the composite outcome. All-cause mortality was compared using Kaplan-Meier estimation and hazard ratios from Cox proportional hazards models. SAS software (version 9.4) was used with overall significance level of 0.05. Results: The sample comprised 1665 patients: age 45.2±12 years, 20.4% male, BMI=48.7±9 kg/m 2, and 63.6% Caucasian. OASH prevalence was 68.5%. OAHS patients were older and more likely to be male with higher BMI, AHI and HbA1c. Although some individual outcomes were higher in OASH vs. non-OASH, findings were not statistically significant: re-intubation (1.5%vs.1.3%, p=0.81) and 30-day readmission (13.8% vs.11.3%, p=0.16). The composite outcome remained significantly associated with OAHS in the multivariable model: OR=1.36, 95%CI:1.005, 1.845. Mortality was 2% in OASH and not significantly higher than non-OAHS (HR=1.39, 95%CI:0.56, 3.42). Conclusion: In this largest sample to date of systematically phenotyped OASH in patients undergoing bariatric surgery, we identify increased post-operative morbidity in those with OASH. Further study is needed to identify whether peri-operative treatment of OASH improves surgical outcomes. Support: